Development of anti-TNF therapy for rheumatoid arthritis. - Feldmann, M (2002)
The aetiology of systemic, autoimmune, chronic inflammatory diseases--such as rheumatoid arthritis--is not known, and their pathogenesis is complex and multifactorial. However, progress in the characterization of intercellular mediators--proteins that are now known as cytokines--has led to the realization that one cytokine, tumour-necrosis factor (TNF; previously known as TNF-alpha), has an important role in the pathogenesis of rheumatoid arthritis. This discovery heralded a new era of targeted and highly effective therapeutics for rheumatoid arthritis and, subsequently, other chronic inflammatory diseases.